Antierótica feroz y otras cuestiones paradójicas - Zúñiga-Rivera, Mónica (Revista Mexicana de Sociología, 2016)
In 2013, Antierótica feroz, a short story collection by Laura Fuentes, was published in Costa Rica. This text came at a time of aesthetic and ideological rupture in the region, since it reflects parody and, at the same time, a certain apology for corporeality and eroticism. This article analyzes some of the ideas in the short story collection, in order to show the approach to eroticism and the worldview proposed. To this end, various positions are studied, ranging from the classic (Bataille), feminist (Preciado) and interdisciplinary (Dadoun) through the scientific (Reich) and even the theological (Althaus-Reid).
Artículo científico
Keywords: Literatura; Género literario; Mujer; Feminismo; Teología